Immigrant Communities and Knowledge Spillovers: Danish-Americans and the Development of the Dairy Industry in the United States - Nina Boberg-Fazlić; Paul Sharp (European Historical Economics Society (EHES), 2019)
Despite the growing literature on the impact of immigration, little is known about the role existing migrant settlements can play for knowledge transmission. We present a case which can illustrate this important mechanism and hypothesize that nineteenth century Danish-American communities helped spread knowledge on modern dairying to rural America. From around 1880, Denmark developed rapidly and by 1890 it was a world-leading dairy producer. Using a difference-in-differences strategy, and data taken from the US census and Danish emigration archives, we find that counties with more Danes in 1880 subsequently both specialized in dairying and used more modern practices.
Keywords: F22; J61; N11; N31; N51; O33; Q16; 330; Dairying; immigration; knowledge spillovers; technology